Effect of cats tail leaves extract (acalypha hispida burm. f.) on wound healing (traumatic ulcer) of wistar male rat oral mucosa (rattus norvegicus) - Sumintarti Sumintarti; Jessica Juliana (DiscoverSys Inc., 2020)
Objective: This study aims to determine the effect of cats tail leaves extract (Acalypha hispida Burm. F.) on wound healing ofWistar male rat mucosa (Rattus norvegicus) as the result of this experimental which obtained later can be used as a reference in dentistry to develop cats tail leaves as an alternative medicine in traumatic ulcer treatment..Material and Methods: This is an experimental research with post-test only control group design.The experimental subject were 24 Wistar male rat divided into four treatment groups, including a 50% A. hispida leaves group, a 75% A. hispida leaves group, a 100% A. hispida leaves group, and povidone iodine control group. All rat in every group were given the treatment and the decrease of wound diameter were measured for 8 days then the data were processed using SPSS program. Results:The average of traumatic wound diameter on 8th day is 0.33±0.41 mm for 50% A. hispida leaves group, 0.50±0.45 mm for 75% A. hispida leaves group, 0.25±0.42 mm for 100% A. hispida leaves group, and 1.17±0.61 mm for control group. Based on Friedman test and Wilcoxon test, the result shows significant difference on wound diameter change in every treatment group. Conclusion: Cats tail leaves extract (acalypha hispida burm. F.) with concentration of 50%, 75%, and 100% have the effect of wound healing on traumatic injury of white rat oral mucosa (rattus novergicus) but there is no significant difference in effectivenessbetween every concentration.